2018
DOI: 10.3390/rs10091395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Static Multibeam Sonar Scanner for 3D Surveys in Confined Underwater Environments

Abstract: Mechanical Sonar Scanning (MSS) is a recent technology that allows sonar to be used for static measurements in the same way as Terrestrial Laser Scanners (TLS), which makes it an attractive tool for underwater infrastructure surveys. Nevertheless, the metrological capabilities of this type of device have been little explored in the literature, particularly in narrow and shallow environments. In this paper, we report on the experimental assessment of a recent MSS, the BlueView BV5000, in a lock. The 3D sonar sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Note that another experiment, dedicated to the assessment of the sensor surveying capacities in a known environment (Moisan et al., 2018) had shown that details smaller than a decimetre could be distinguished, which is consistent with what can be observed here. Defects of significant size in the masonry, such as missing stones or cavities, are easily detected, while finer details, such as damaged joints, are more difficult to distinguish.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Note that another experiment, dedicated to the assessment of the sensor surveying capacities in a known environment (Moisan et al., 2018) had shown that details smaller than a decimetre could be distinguished, which is consistent with what can be observed here. Defects of significant size in the masonry, such as missing stones or cavities, are easily detected, while finer details, such as damaged joints, are more difficult to distinguish.…”
Section: Resultssupporting
confidence: 90%
“…In addition, some defects are probably related to acoustic phenomena, as noticed in Moisan et al. (2018).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…It is necessary to highlight the importance of using accurate equipment to capture and model structural and surface deformations on an accurate basis. This can be clearly understood through the work by Moisan et al [19], who evaluate an alternative and recent technique for 3D surveys in confined underwater environments: the Mechanical Sonar Scanning (MSS). Obviously, MSS is aimed at producing point cloud data of, for instance, underwater infrastructure, but its comparison with the accuracy of TLS in the same case study-when no water is present-reveals its crucial role for surface deformations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data from the two types of sensors were aligned to construct a full 3D reference model of a canal tunnel. A BV5000 precision test was also conducted in [ 17 ]. The accuracy of the laser data was measured in centimeters so that it could be used as a reference with which to compare the BV5000 data.…”
Section: Introductionmentioning
confidence: 99%